2008
DOI: 10.1093/ndt/gfn372
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of peritoneal dialysis practice patterns and outcomes between a Canadian and a Chinese centre

Abstract: Patient characteristics, dialysis practice patterns and outcomes vary between Canadian and Chinese patients. The variability in patient outcomes between these two centres indicates that further improvements may be possible in both centres. We have identified several areas for improving outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
3
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 29 publications
5
55
3
2
Order By: Relevance
“…Contrary to our previous report and other reports with long-term observation (17,18), the present study showed that catheter dysfunction was the leading cause of technique failure (followed by peritonitis) in patients starting PD soon after catheter insertion. The incidence of catheter dysfunction requiring transfer to HD was higher in BI ≤7 patients than in BI >14 patients.…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to our previous report and other reports with long-term observation (17,18), the present study showed that catheter dysfunction was the leading cause of technique failure (followed by peritonitis) in patients starting PD soon after catheter insertion. The incidence of catheter dysfunction requiring transfer to HD was higher in BI ≤7 patients than in BI >14 patients.…”
Section: Discussioncontrasting
confidence: 99%
“…8 Our data showed that age, gender, diabetes, and the time of dialysis had no significant associations with the occurrence Implementation of CQI in peritonitis study 1031 of peritonitis, which was consistent with previous studies. 4 However, gastrointestinal tract dysfunction and nonstandard procedures are common causes of peritonitis.…”
Section: Discussionsupporting
confidence: 92%
“…Single centers have reported the incidence of peritonitis up to once every 60 patient months. 8,12 Analysis of peritonitis-associated microbial species showed a high incidence of Gram-positive cocci, which may be associated with nonstandard procedures. Patients were discharged from the hospital unless they and their family members passed the examination on aseptic operations, and the operation was checked again at the re-examination to correct the improper procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Specific guidelines for treating peritonitis were updated and published in 2010 (21), as were guidelines for PD 615 PDI NovEMBER 2011 -voL. 31,No. 6 ISPD: REDUCING THE RISKS OF PD-RELATED INFECTIONS catheter insertion and management (22).…”
Section: Special Articlementioning
confidence: 99%